(untitled) (Research, Society and Development, 2021)
The intensive use of natural resources has caused increasing impacts on the environment. Water is one of the most affected resources, because the various human activities depend on it for its operation, and this endangers its availability in quantity and quality. On the possibility of scarcity, it was necessary to recognize water as a limited natural resource and, therefore, endowed with economic value. The water use charge instrument is based on this principle, established by Law 9.433/1997, which established the National Water Resources Policy. The present work had as objective the study of this instrument, particularly in waters under the domain of the Doce River Basin Union. The research was based on the collection, systematization and interpretation of information through documentary and bibliographical research. The results showed that despite the advances made with the instrument, there are still limitations to be resolved, such as default in the basin under study, insufficient amounts collected to perform actions in the watershed and low efficiency of disbursed resources. Thus, an environment of constant consolidation and improvement of the instrument should be created, in fact to induce and stimulate conservation, integrated management and recovery of water resources.